2018
DOI: 10.1002/rrq.229
|View full text |Cite
|
Sign up to set email alerts
|

A Synthesis of Quantitative Research on Reading Programs for Secondary Students

Abstract: A B S T R A C TRecent initiatives in the United States and United Kingdom have added greatly to the amount and quality of research on the effectiveness of secondary reading programs, especially programs for struggling readers. In this review of the experimental research on secondary reading programs, the authors focused on 69 studies that used random assignment (n = 62) or high-quality quasi-experiments (n = 7) to evaluate outcomes of 51 programs on widely accepted measures of reading. Categories of programs u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 72 publications
5
91
0
Order By: Relevance
“…Perhaps reflecting recent technologies, Cheung and Slavin's (2013) synthesis of 20 studies regarding educational technology for elementary school reading showed relatively larger but still small effects (ES = 0.14). However, a recent review of reading programs for secondary students (Baye et al, 2018), with 23 programs including technology and 46 not, showed no advantage of technology-enhanced programs (ES = −0.01). These effect sizes provide a range for which to interpret the effects of GG on students' learning.…”
Section: Small Effects For Readersmentioning
confidence: 98%
See 1 more Smart Citation
“…Perhaps reflecting recent technologies, Cheung and Slavin's (2013) synthesis of 20 studies regarding educational technology for elementary school reading showed relatively larger but still small effects (ES = 0.14). However, a recent review of reading programs for secondary students (Baye et al, 2018), with 23 programs including technology and 46 not, showed no advantage of technology-enhanced programs (ES = −0.01). These effect sizes provide a range for which to interpret the effects of GG on students' learning.…”
Section: Small Effects For Readersmentioning
confidence: 98%
“…Transitioning to literacy specifically, reviews considering literacy learning with technology (Baye et al, 2018;Cheung & Slavin, 2013;Slavin et al, 2011) and largescale evaluation studies from the United States (Campuzano, Dynarski, Agodini, & Rall, 2009;Dynarski et al, 2007), the United Kingdom , and Australia (Parr & Fung, 2000) are most connected to our review. However, compared with the more general learning with technology, these provide less optimistic predictions for educational technology and serious games for reading, such as GG.…”
Section: Learning Literacy With Computer Supportmentioning
confidence: 99%
“…Put simply, students read far more in those 12 weeks than they had ever done before, and the faster read of two whole novels in effect provided a catch‐up programme for poorer readers from both groups in the English classroom with their peers, not marginalised in a remedial programme (Baye et al, ). In these contexts, poorer readers were repositioned as good readers, heightening teachers' expectations of their reading capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, FR + T teachers remediated students' sticking points through using the full range of comprehension strategies at the point of need in a more active ‘reading aloud’; graphic organisers supported students to understand the whole text, and seating students sociably in groups created inclusive communities of engaged and motivated readers (Oakhill et al, ; Sutherland, ). This was direct instruction in the context of a faster read of whole texts, integrated with cooperative learning, professional development and a flexible pedagogy, all four categories seen as effective in meta‐analyses of secondary reading programmes (Baye et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Effective interventions, key competencies, and assessment Regarding the assessment of basic knowledge and skills-such as vocabulary and grammar knowledge, as well as reading and writing ability-there is a well-established scientific literature and growing base of evidence on proven programs (see Baye et al, 2019;Graham & Hebert, 2011;Graham et al, 2012;Slavin et al, 2010Slavin et al, , 2019. However, the assessment of competencies with a more complex, multidimensional nature poses different issues.…”
Section: Ecnu Review Of Educationmentioning
confidence: 99%